Perbedaan Pengetahuan Tehnik Menyusui Sebelum dan Sesudah Penyuluhan - Siti Faridah (Indonesian Journal for Health Sciences, 2017)
Maternal knowledge related the right technique of breastfeeding is the step to achieve exclusive breastfeeding successfully. The right knowledge will lead to good breastfeeding technique. This study aimed to determinate the differences in knowledge related the right technique of breastfeeding before and after counseling. The method of this study was descriptive, by 24 samples of breastfeeding mothers with accidental sampling technique. Data was analyzed by Wilcoxon test data analysis. Results of this study showed that before counseling there was 50% breastfeeding mothers had good knowledge related the right technique of breastfeeding, and after counseling, there was 58,33%. There were significant differences in knowledge about exclusive breastfeeding before and after counseling. And there were significant differences related the right technique of breastfeeding, before and after counseling. Mothers are expected to actively seek for the information in order to avoid problems during breastfeeding.